2012
DOI: 10.3168/jds.2011-4881
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Evaluation of bulk tank milk microbiological quality of nine dairy farms in Tennessee

Abstract: The purpose of this study was to evaluate the bulk tank milk (BTM) quality of 9 East Tennessee dairy farms and to determine its relationship with selected quality milk parameters. Bulk tank milk samples (n=1,141) were collected over a 42-mo period (June 2006 through November 2009) from farms, based on their preliminary incubation count (PIC) history. Parameters of BTM quality evaluated in this study included somatic cell count (SCC), standard plate count (SPC), PIC, laboratory pasteurization count (LPC), Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 8 publications
5
22
3
1
Order By: Relevance
“…Both Staphylococcus and Streptococcus were detected at the highest levels in milk overall, and the populations of both were significantly enriched in the summer season. This result is in agreement with culture-based studies that have similarly found high numbers of Streptococcus in either the summer or winter (4547). …”
Section: Discussionsupporting
confidence: 92%
“…Both Staphylococcus and Streptococcus were detected at the highest levels in milk overall, and the populations of both were significantly enriched in the summer season. This result is in agreement with culture-based studies that have similarly found high numbers of Streptococcus in either the summer or winter (4547). …”
Section: Discussionsupporting
confidence: 92%
“…Increased SCC in the milk should not be underestimated as they are followed by the multi-dimensional negative effect related to animal heath and farmer profitability. Previous study has shown that season trends influence the somatic cells count in USA and Canada [20,21]. While in our work we haven't seen any difference between months.…”
Section: Discussioncontrasting
confidence: 65%
“…The existence of coliform shows nonsufficient sanitation and hygiene applications in milking, storage and carriage process (Chye et al , 2004; Pantoja et al , 2009). Unclean udders (Pantoja et al , 2009), soil, manure and soiled water are important causes for increasing coliform counts in the milk (Gillespie et al , 2012). …”
Section: Resultsmentioning
confidence: 99%
“…The count of coliform bacteria is an indicator of fecal contamination in the raw milk (Worku et al , 2012). Coliform bacteria can contaminate milk by dirty udders and tears (Cicconi-Hogan et al , 2013a; Pantoja et al , 2009), soiled water, feces of mouse and bird, insects, dust, unsanitary equipments (Gillespie et al , 2012) and mastitis (Cicconi-Hogan et al , 2013a; Worku et al , 2012). Staphylococcus aureus ( S. aureus ) is a pathogen for human and some animal species.…”
Section: Introductionmentioning
confidence: 99%